2021
DOI: 10.3390/app11020744
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Algorithm Based Deep Learning Neural Network Structure and Hyperparameter Optimization

Abstract: Alzheimer’s disease is one of the major challenges of population ageing, and diagnosis and prediction of the disease through various biomarkers is the key. While the application of deep learning as imaging technologies has recently expanded across the medical industry, empirical design of these technologies is very difficult. The main reason for this problem is that the performance of the Convolutional Neural Networks (CNN) differ greatly depending on the statistical distribution of the input dataset. Differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(23 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…The proposed strategy achieved an accuracy of 93.5%. A study [40] applied network architecture and hyperparameters optimization based on a Genetic Algorithm. They used an amyloid brain image dataset that contains PET/CT images of 414 patients.…”
Section: Related Studiesmentioning
confidence: 99%
“…The proposed strategy achieved an accuracy of 93.5%. A study [40] applied network architecture and hyperparameters optimization based on a Genetic Algorithm. They used an amyloid brain image dataset that contains PET/CT images of 414 patients.…”
Section: Related Studiesmentioning
confidence: 99%
“…Lee et al [23] applied the genetic algorithm on CNN using both network configuration and hyperparameters. They showed that their algorithm outperformed genetic CNN by 11.74% on an amyloid brain image dataset used for Alzheimer's disease diagnosis.…”
Section: Related Workmentioning
confidence: 99%
“…Although ANN is used to predict the solution for the given inputs, genetic algorithms are strongly focused on the optimization of the problem. Several applications based on genetic algorithms have shown their applicability in chemical engineering [80] and biotechnology [81], among other fields.…”
Section: Machine Learning For Plastic Pyrolysismentioning
confidence: 99%